Successful therapy in unusual generalized Dermatophilus congolensis infection in a calf based on modified in vitro disk diffusion test - Domingues, Paulo Francisco [UNESP]; Guerra, Simony Trevizan [UNESP]; Paula, Carolina Lechinski De [UNESP]; Alves, Ana Carolina [UNESP]; Bolanos, Carmen Alicia Daza [UNESP]; Morais, Amanda Bonalume Cordeiro De [UNESP]; Risseti, Rafaela Mastrangelo [UNESP]; Colhado, Bruna Da Silva [UNESP]; Portilho, Fábio Vinicius Ramos [UNESP]; Caxito, Marília Salgado [UNESP]; Listoni, Fernando José Paganini [UNESP]; Oliveira, Daniel Ornelas De [UNESP]; et al. (Instituto Biológico, 2018)
Bovine dermatophilosis is a dermatitis characterized by typical focal or localized lesions with “paintbrush” aspect and occasionally as disseminated cutaneous disease. We report the case of a one-year-old Nelore female with history of chronic cutaneous disseminated lesions that appeared immediately after a rainfall period. Serous to purulent exudates, hair with tufted appearance, hyperkeratotic, non-pruritic, hardened, yellowish to brown, and coalescent crusty lesions were observed distributed all over its body. Removal of the crusts revealed ulcerated or hemorrhagic areas, with irregular elevated crusts like “paintbrush”. Microbiological diagnosis enabled the identification of a microorganism, the Dermatophilus congolensis. Despite disseminated and chronic lesions, we obtained a successful therapy with parenteral therapy using long-acting tetracycline based on modified in vitro disk diffusion test. The present report highlights success therapy in uncommon generalized bovine dermatophilosis with selection of first-choice drugs based on modified in vitro susceptibility test, and need of responsible use of antimicrobials in livestock.

A dermatofilose bovina é uma dermatite caracterizada por lesões focais ou localizadas com aspecto de “pincel” e, ocasionalmente, como lesão cutânea disseminada. Relata-se o caso de uma fêmea bovina de um ano de idade, que foi atendida apresentando história de lesões cutâneas crônicas imediatamente após um período de alta pluviosidade. Ao exame clínico, lesões serosas a purulentas, com hiperqueratose, coalescentes, não pruriginosas, ressecadas, de coloração amarelada à acinzentada foram observadas distribuídas de modo generalizado pelo animal. A remoção das crostas revelou áreas ulceradas ou hemorrágicas, com crostas irregulares e elevadas semelhantes a “pincel”. O diagnóstico microbiológico possibilitou a identificação do micro-organismo Dermatophilus congolensis. Apesar das lesões disseminadas e crônicas, a cura do animal foi obtida com tratamento parenteral usando oxitetraciclina de longa duração, baseado em teste in vitro de sensibilidade microbiana modificado. O presente relato ressalta o sucesso no tratamento de caso incomum de lesões generalizadas de dermatofilose bovina com respaldo de teste in vitro de sensibilidade modificado, bem como a necessidade do uso responsável de antimicrobianos em animais de produção.
Sucesso no tratamento de infecção generalizada em bezerra por Dermatophilus congolensis baseado em teste in vitro modificado de difusão com discos
Keywords: dermatophilosis; bovine; treatment; in vitro susceptibility pattern; oxytetracycline; dermatofilose; bovinos; tratamento; teste de sensibilidade microbiana in vitro; oxitetraciclina